Remediation of 2, 4, 6-trinitrotoluene Persistent in the Environment – A review. Issue 1 (2nd January 2020) - A, Thenmozhi; M, Devasena
ABSTRACT: Nitroaromatic explosives such as trinitrotoluene (TNT), dinitrotluene (DNT) and other metabolites present the greatest concern to the environment and public health due to their mutagenic properties and persistence. Remediation of soil contaminated by explosive residues has received increased interest in recent years in many countries due to their prolific use since the World War I and II. There is an urgent need to identify appropriate and effective technologies to attenuate/remediate TNT-contaminated sites and ensure safe environment. This article presents an overview of the technologies commonly adopted for remediation of TNT contaminated sites with particular emphasis on ways to enhance biodegradation especially with the addition of surfactants or biosurfactants.